Correlating process and product data to get an insight into translation difficulty. - Vanroy, Bram; De Clercq, Orphée; Macken, Lieve (Perspectives: Studies in Translatology, 2019)
Research in the field of translation studies suggests that translation product features can indicate translation difficulty. In the current pilot study, we investigate three of these features, namely the number of errors made in a translation, word translation entropy and degree of syntactic equivalence. We correlate these translation product features with translation process features that can be put together into three categories: duration, revision and gaze information. These features serve as a proxy for the cognitive effort required to solve difficulties in translation. The data that we used was gathered from professional translators as well as students of translation studies. The product data contains manual error annotations of the translations, automatically calculated entropy values and syntactic re-ordering metrics. The process data are derived from keystroke and eye-tracking data gathered during the translation process. By correlating product and process data, we inspect how translation difficulty is reflected in the translation process and whether it is feasible to use product features to predict difficulties in translation. In addition, we also compare data of professional translators and students. We will show that correlations between process and product features exist, which opens many doors to further research on translatability.